2020
DOI: 10.1002/adom.202000822
|View full text |Cite
|
Sign up to set email alerts
|

Photochromic Mechanism and Dual‐Phase Formation in Oxygen‐Containing Rare‐Earth Hydride Thin Films

Abstract: The photochromic effect was also observed in oxygen-containing gadolinium, dysprosium as well as erbium hydride and it has been concluded that reactively sputtered lanthanide-based hydrides behave similarly as the yttriumbased thin films, suggesting a common physical mechanism of the photochromic effect. [3] Based on charge neutrality considerations, the authors suggested a single-phase structure and introduced the term "metal oxyhydrides," [3] whereas previously such photochromic thin films were referred to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 29 publications
7
25
1
Order By: Relevance
“…The fact that we could rationalize (i) composition, (ii) optical transmittance, (iii) optical bandgap, (iv) lattice constant, and (v) trends in photochromic properties within the framework of a single-phase line-compound strongly indicates that the photochromism is an intrinsic property of the REO x H 3–2 x oxyhydride phase. We note that the alternative hypothesis of Hans et al, 31 who recently proposed the coexistence of an oxide and a dihydride phase, is not compatible with the well-established optical bandgaps and complete transmittance for E < E g of REO x H 3–2 x thin films. Conversely, our careful study of the oxidation behavior and its dependency on the deposition pressure can explain the specific composition reported by Hans et al as that of a partially oxidized REH 2 , a nongeneral case that we obtain only around p *.…”
contrasting
confidence: 80%
“…The fact that we could rationalize (i) composition, (ii) optical transmittance, (iii) optical bandgap, (iv) lattice constant, and (v) trends in photochromic properties within the framework of a single-phase line-compound strongly indicates that the photochromism is an intrinsic property of the REO x H 3–2 x oxyhydride phase. We note that the alternative hypothesis of Hans et al, 31 who recently proposed the coexistence of an oxide and a dihydride phase, is not compatible with the well-established optical bandgaps and complete transmittance for E < E g of REO x H 3–2 x thin films. Conversely, our careful study of the oxidation behavior and its dependency on the deposition pressure can explain the specific composition reported by Hans et al as that of a partially oxidized REH 2 , a nongeneral case that we obtain only around p *.…”
contrasting
confidence: 80%
“…changes in the structure or electronic rearrangements. In our recent work [16] , we have observed a columnar-type structure and a coexistence of fcc REH2-like and bixbyite-like RE2(HxOy)3 phases with compressive residual stress on the order of GPa in the films. As it is known that yttrium hydride is photochromic at high pressures [17] we propose a similar mechanism of photodarkening in REHO, accompanied by a photon-induced hydrogen transfer from the bixbyite RE2O3 phase into the fcc REH2 phase.…”
Section: Introductionmentioning
confidence: 85%
“…In YHO thin films, it was recently suggested that oxygen out‐diffusion from the lattice followed by formation of metallic YHO domains is necessary for the photodarkening process. [ 18,19 ] In contrast, it was proposed that photon‐induced hydrogen transfer between phases [ 22,23 ] could also explain the photochromic mechanism. In either case, the ability of the films to achieve the darkened state at 5 K suggests that anion transfer is not responsible for this process at low temperatures.…”
Section: Figurementioning
confidence: 99%